2016
DOI: 10.5392/jkca.2016.16.07.112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brand Storytelling based on the Subject of Story

Abstract: The purpose of this research is to examine the effect of storytelling ads. To find out the effect, three different ads were created; one is no storytelling in ads, another is corporate storytelling ads, and the other is client storytelling ads. Each ads was exposed to high school students, and we analyzed their response to the ads such as ads recall, attitude toward ads, emotional response to ads, purchase intention, and the intention of word-of-mouth. The results showed that corporate storytelling ads among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Data findings from the questions related to consumer-based stories concluded that most of the respondents agree that they engage with airline brands in Malaysia through consumer-based stories (mean = 3.88) compared to brand history. In addition, the data also supported the study by Hong and Cho (2016) that people who were exposed to a non-story ad showed the highest negative emotion while those who were exposed to consumer-based telling advertisement had the lowest negative emotion towards the brand. For instance, Coca-Cola is one of the world's valuable brands that is widely known for its powerful brand storytelling techniques to engage with customers (Plessis, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Data findings from the questions related to consumer-based stories concluded that most of the respondents agree that they engage with airline brands in Malaysia through consumer-based stories (mean = 3.88) compared to brand history. In addition, the data also supported the study by Hong and Cho (2016) that people who were exposed to a non-story ad showed the highest negative emotion while those who were exposed to consumer-based telling advertisement had the lowest negative emotion towards the brand. For instance, Coca-Cola is one of the world's valuable brands that is widely known for its powerful brand storytelling techniques to engage with customers (Plessis, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…(Lundqvist et al, 2013) found the power of storytelling in a consumer's experience. (Hong, S.Y., & Cho, 2016) show that stories about a brand are strongly influenced by the subject of the story. Meanwhile, (Moore, 2011), conducted research which found that tinular speech about a brand can influence the storyteller in an advertisement.…”
Section: Triangulation Results With Sourcesmentioning
confidence: 99%
“…Three different types of advertisements were designed based on storyteller types (Hong and Cho, 2016): founder’s story, consumer’s story and an informational ad. Each ad was recorded both with male and female voices.…”
Section: Methodsmentioning
confidence: 99%